Perancangan Pengukuran Kinerja di PT Sayuran Siap Saji dengan Pendekatan Balanced Scorecard - Tartiani, Yuni Astuti Tri; Sumarwan, Ujang; Sahara, - (Institut Pertanian Bogor, 2019)
PT Sayuran Siap Saji is one of the fresh cut vegetable supplier companies that are developing. In maintaining existence as a result of increasingly fierce business competition, PT X needs to continue to improve its performance. The objectives of the research were to built performance measurement at PT Sayuran Siap Saji using Balanced Scorecard (BSC). BSC is a management tool in measuring performance comprehensively. This research used descriptive techniques through case studies. Determination of resource persons is done by purposive sampling method, namely five experts from the management of PT Sayuran Siap Saji. The data was collected through in-depth interview techniques, structured interviews using questionnaires and literature study. There were four perspectives that became variables in this research, which were financial perspective, customer perspective, internal business process perspective and growth and learning perspective. Analytic Hierarchy Process (AHP) was used to determined the perspective priority and strategic objectives of Balanced Scorecard. The result showed that in the customer perspective, four strategic objectives were identified and five strategic objectives for each of financial perspectives, internal business process perspectives and learning and growth perspectives were identified. In the customer perspective, enhancement of satisfaction and trust from customers shows the highest contribution, meanwhile in the financial perspective, fulfill the requirements to the supplier shows the highest contribution. In the growth and learning perspective, enhancement of the capabilities and the development of the human resources shows the highest contribution, and in the internal business process perspective, product and production process in accordance with the standards shows the highest contribution to the companies performance. This means that the four strategic objectives of each perspective that have the highest contribution are the basis for determining targets and better strategic initiatives for companies in maintaining and improving their performance